2021
DOI: 10.1103/physrevmaterials.5.l061401
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetoionic control of perpendicular exchange bias

Abstract: We demonstrate reversible voltage control of perpendicular exchange bias via H + pumping in a NiO/Pd/Co/Pd/Gd(OH) 3 /Au heterostructure at room temperature. The perpendicular exchange bias results from a tailored layer structure consisting of an antiferromagnetic NiO layer and a ferromagnetic Co layer, stabilized by an ultrathin Pd interlayer. Voltage mediated H + pumping through the Gd(OH) 3 layer and subsequent H absorption at the Pd/Co interface leads to a decrease in the perpendicular anisotropy. In conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Spin textures, such as skyrmions, 112,113 chiral domain walls, 114,115 and spin spirals, 116,117 are stabilized under the Dzyaloshinskii-Moriya interaction (DMI), which have been shown to be tunable using magnetoionics, [118][119][120][121] with possible applications in spin-orbitronics. 122 Continued fundamental research has led to further exploration of different structures, materials, and mobile ions, with successful demonstration of magneto-ionic effects using hydrogen, 118,[123][124][125] lithium, [126][127][128][129][130] nitrogen, [131][132][133] and flourine. 134 The last two years have seen a flurry of exciting activity, a few of which are highlighted in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spin textures, such as skyrmions, 112,113 chiral domain walls, 114,115 and spin spirals, 116,117 are stabilized under the Dzyaloshinskii-Moriya interaction (DMI), which have been shown to be tunable using magnetoionics, [118][119][120][121] with possible applications in spin-orbitronics. 122 Continued fundamental research has led to further exploration of different structures, materials, and mobile ions, with successful demonstration of magneto-ionic effects using hydrogen, 118,[123][124][125] lithium, [126][127][128][129][130] nitrogen, [131][132][133] and flourine. 134 The last two years have seen a flurry of exciting activity, a few of which are highlighted in Fig.…”
mentioning
confidence: 99%
“…135 Yi et al 91 reported reversible and nonvolatile phase transitions at room temperature under voltage using both H þ and O 2À ions in digital complex oxides, showing that nondestructive structural changes under bias are possible [Fig. 2 125,137,138 Chen et al 118 reported inducing Dzyaloshinskii-Moriya interaction by chemisorption and desorption of H þ , seen in reversible and nonvolatile chirality transitions of magnetic domain walls [Fig. 2(c)].…”
mentioning
confidence: 99%
“…Voltage control of magnetism via ion migration, or magneto-ionics, has emerged as a promising approach because the magnetic response to small voltages can be very strong compared to that of other magnetoelectric coupling mechanisms based on strain, exchange coupling, or charge carrier modulation. [10,11] Magneto-ionics utilizing oxygen or hydrogen ions has been shown to alter the magnetic anisotropy, [12][13][14][15][16][17] exchange bias, [18,19,20] saturation magnetization, [12][13][14][15][16][17][21][22][23] Curie temperature, [21] Dyaloshinskii-Moriya interaction (DMI), [24] ferrimagnetic order, [25] and ferromagnetic resonance. [26] The use of lithium ions has also attracted interest because of their small size, the capacity for reversible intercalation, and fast diffusion kinetics.…”
mentioning
confidence: 99%
“…9,10 Magneto-ionics have allowed the tuning of a number of magnetic functionalities such as magnetization, 6 perpendicular magnetic anisotropy, 7,[11][12][13] coercivity, 14 domain wall velocity, 15 superconductivity, 16,17 Dzyaloshinskii-Moriya interaction (DMI) and spin textures, 11,[18][19][20] ferrimagnetic order, 21 and exchange bias. 10,22,23 There have also been recent interests in alterative ionic systems, e.g., based on hydrogen or nitrogen, 24,25 that exhibit different ionic migration characteristics.…”
mentioning
confidence: 99%